2012
DOI: 10.1021/la300810q
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Air–Water Interfacial Properties of Biodegradable Polyesters and Their Block Copolymers with Poly(ethylene glycol)

Abstract: It has been reported that the surface pressure–area isotherm of poly(d,l-lactic acid-ran-glycolic acid) (PLGA) at the air–water interface exhibits several interesting features: (1) a plateau at intermediate compression levels, (2) a sharp rise in surface pressure upon further compression, and (3) marked surface pressure–area hysteresis during compression–expansion cycles. To investigate the molecular origin of this behavior, we conducted an extensive set of surface pressure and AFM imaging measurements with PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
89
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(96 citation statements)
references
References 45 publications
7
89
0
Order By: Relevance
“…30 We attribute, the hysteresis manifested upon film expansion to the viscoelastic behavior of polymer film. 30 Figure 2(c) shows that the intersection of linear extrapolation of steep Π- A region with the plateau region may yield the limiting surface area at which the aqueous area is just fully covered by polymers and Π starts to rise steeply. The isotherms of PI 2 DTEC differ significantly from those of PDTEC in some respects.…”
Section: Resultsmentioning
confidence: 92%
“…30 We attribute, the hysteresis manifested upon film expansion to the viscoelastic behavior of polymer film. 30 Figure 2(c) shows that the intersection of linear extrapolation of steep Π- A region with the plateau region may yield the limiting surface area at which the aqueous area is just fully covered by polymers and Π starts to rise steeply. The isotherms of PI 2 DTEC differ significantly from those of PDTEC in some respects.…”
Section: Resultsmentioning
confidence: 92%
“…In a previous publication, 14 we speculated that the exponential rise in surface pressure observed at low film areas originates from the interconnected glassy PLGA domains that form within the polymer film under high compression. However, this understanding is incomplete; as will be demonstrated by the data presented in this subsection, the change in the PLGA structurewhatever it is -that causes the surface pressure upturn is produced only during compression (and as shown in Figure S4 that change is only short lived afterwards if the compression is stopped).…”
Section: Dynamic Nature Of the Surface Pressure Increase At High Compmentioning
confidence: 91%
“…4,14 From the results of these studies we concluded that Langmuir PLGA (Group II) films typically exhibit rapid increases in surface pressure under high compression because of a transformation of the material into a glassy state. This explanation was also supported by the observation that a Langmuir film formed by poly(D,L-lactic acid-ran-glycolic acid-ran-caprolactone) (PLGACL), which is similar in chemical structure to PLGA but is non-glassy due to the presence of the caprolactone co- Millipore-purified water (18 MΩ·cm resistivity) was used as the subphase.…”
mentioning
confidence: 99%
“…In the case of flat surfaces, the thickness of PEG layers has been determined with X-ray photoelectron spectroscopy (XPS), ellipsometry, 37 and atomic force microscopy (AFM). 80 Direct structural information about the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 15 location of proteins has been obtained with reflectometric interference spectroscopy (RIfS) and neutron reflectometry. 81 The reflectrometry studies revealed that proteins can only penetrate into PEG layers of low grafting density.…”
mentioning
confidence: 99%